1994
DOI: 10.1101/gad.8.12.1379
|View full text |Cite
|
Sign up to set email alerts
|

The yeast homolog of H < beta > 58, a mouse gene essential for embryogenesis, performs a role in the delivery of proteins to the vacuole.

Abstract: The highly conserved and ubiquitously expressed mouse gene H<1~>58, identified through insertional mutagenesis, has been shown to be essential for early postimplantation development in mouse, but the mechanism by which it acts is unknown (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…Therefore, a domain swap experiment was performed in which the C-terminal third of Vps26p was replaced with the homologous region of H␤58, the mouse homolog. This Vps26p-H␤58 hybrid has been shown previously to fully complement the CPY sorting defect in a vps26⌬ cell (Bachhawat et al, 1994). We also found this to be the case; however, to our surprise we found that the presence of an HA tag in the N-terminal half of the protein rendered the Vps26p-HA-H␤58 hybrid completely nonfunctional ( Figure 4B).…”
Section: Figurementioning
confidence: 39%
See 1 more Smart Citation
“…Therefore, a domain swap experiment was performed in which the C-terminal third of Vps26p was replaced with the homologous region of H␤58, the mouse homolog. This Vps26p-H␤58 hybrid has been shown previously to fully complement the CPY sorting defect in a vps26⌬ cell (Bachhawat et al, 1994). We also found this to be the case; however, to our surprise we found that the presence of an HA tag in the N-terminal half of the protein rendered the Vps26p-HA-H␤58 hybrid completely nonfunctional ( Figure 4B).…”
Section: Figurementioning
confidence: 39%
“…Replacing the carboxy terminus of Vps26p with the homologous region of the mouse homolog H␤58 resulted in a hybrid molecule that was fully functional. This hybrid construct was also generated by Jones and colleagues and was reported to be fully functional in its ability to complement CPY sorting in a vps26 mutant (Bachhawat et al, 1994). To facilitate detection of the hybrid construct a HA epitope-tagged construct, in which a triple HA tag was inserted between residues 76/77, was used as the basis for this hybrid construct.…”
Section: Role Of Vps26p In Retromer Functionmentioning
confidence: 98%
“…The plasmids used in this study are listed in Table 1. pSN269 is pBluescript KS ϩ (Stratagene, La Jolla, Calif.) with a 2.0-kbp XhoI-XbaI PCR-generated insert consisting of the entire PEP8 gene (2) in which the PEP8 open reading frame was precisely replaced with the LEU2 gene. pSN273 was constructed by subcloning the 3.0-kbp SacI-XhoI fragment from pTS17 (1) into the SacI-XhoI sites of pBluescript KS ϩ .…”
Section: Methodsmentioning
confidence: 99%
“…SNX1 binds to the cytoplasmic tail of the epidermal growth factorreceptor (EGFR) (17) where it may play a role in endosome to lysosome trafficking. The Vps26p protein (18) is homologous to mouse H␤58 which is essential for completing embryogenesis (19).…”
mentioning
confidence: 99%